Outcomes of Patients Who Have Do Not Resuscitate Status prior to Being Admitted to an Intensive Care Unit - Debjit Saha; Carlos Moreno; Marc Csete; Elizabeth Kury Perez; Luigi Cubeddu; David Farcy; Steven Henry; Zachary Glazer; Lisa A. Moreno-Walton; Robert C. Goldszer (Scientifica)
Admission of patients who have do not resuscitate (DNR) status to an intensive care unit (ICU) is potentially a misallocation of limited resources to patients who may neither need nor want intensive care. Yet, patients who have DNR status are often admitted to the ICU. This is a retrospective review of patients who had a valid DNR status at the time that they were admitted to an ICU in a single hospital over an eighteen-month period. Thirty-five patients met the criteria for inclusion in the study. The primary reasons for admission to the ICU were respiratory distress (54.2%) and sepsis (45.7%). Sixteen (45.7%) of the patients died, compared to a 5.4% mortality rate for all patients admitted to our ICU during this period (p<0.001). APACHE II score was a significant predictor of mortality (18.5 ± 1.3 alive and 23.4 ± 1.4 dead; p=0.038). Of the 19 patients discharged alive, 9 were discharged home, 5 to hospice, and 4 to a post-acute care facility. Conclusions. Patients who have DNR status and are admitted to the ICU have a higher mortality than other ICU patients. Those who survive have a high likelihood of being discharged to hospice or a post-acute care facility. The value of intensive intervention for these patients is not supported by these results. Only a minority of patients were seen by palliative care and chaplain teams, services which the literature supports as valuable for DNR patients. Our study supports the need for less expensive and less intensive but more appropriate resources for patients and families who have chosen DNR status.